Partially mummified remains of a 3rd century AD individual from the Eastern desert in Egypt : a paleopathological case study - Pálfi, György (Acta Biologica Szegediensis, 2012)
Our study deals with the partially mummified remains of an adult individual recovered in the Eastern Desert of Egypt in 2007, during the excavations of the Roman praesidium of Dios. The grave was discovered in the rubbish dump of the fortification. Several elements of the lower limb are mummified. However, the lack of mummification or more precisely the partial state of mummification of some parts enables the direct observation of the bones and the identification of several paleopathological conditions. Among others, dental pathologies and associated maxillary infection, severe osteoarthrosis and a very advanced stage, OPLL-associated DISH (Resnick et al. 1978) have been identified.